Economic and Investment Opportunities in Local Level: Exploring Economic Development in an Indonesian Regency - Husnah Husnah; Mohamad Ichwan Ichwan (Research Horizon, 2023)
The increase in investment is essential to accelerate national economic development and achieve Indonesia's political and economic sovereignty. This study focuses on the significance of increased investment to foster national economic development and achieve Indonesia's political and economic sovereignty. Its primary aim is to assess the investment potential in Buol Regency. The research draws on both primary data from surveys and focus group discussions across sub-districts, as well as secondary data from reputable sources like the Central Bureau of Statistics (BPS) and relevant government agencies concerning investment in the region. The findings underscore the existence of substantial economic potential and investment opportunities in Buol Regency, with notable prospects in the food, infrastructure, and energy sectors. To effectively harness these opportunities, the formulation of comprehensive investment policies is imperative, encompassing strategic steps to fully realize the benefits of investment in Buol Regency.